A survey of state medical licensing boards: can the travelling team physician practice in your state?. Issue 1 (4th October 2012) - Viola, Tracey; Carlson, Chad; Trojian, Thomas H; Anderson, Jeffrey
Abstract : This was a study that surveyed state medical licensing boards in the USA, to see if they have laws or exemptions for travelling team physicians to practice medicine on their own team, while travelling to that state. Surveys were sent to 58 medical boards, with legislative data being obtained for 54. Eighteen states (33%) allow team physicians travelling with their team to practice medicine with their home-state license. Thirty-six states (67%) do not have a legal pathway to allow the practice of medicine without a license: 27 (50%) do not allow the practice of medicine without a license from their state, 6 (11%) have an exemption for a 'consultant' to act in concert with a home-state physician (though this is not applicable to the team physician) and 3 (6%) do not have an exemption, but recognise that it happens without their involvement. A second survey was sent to 20 malpractice carriers, identified by an internet search to represent a diverse sample, to see if these companies offered policies that would cover the team physician, and if they also had licensure requirements. Of the 11 that responded, only 2 companies would provide coverage regardless of individual state licensing requirements, 5 companies would provide coverage to a provider who travels, but would require the provider to be licensed in any state they travel to and 4 companies would not provide coverage out of the home state, regardless of licensure. The American Medical Society for Sports Medicine is working on a Federal patch for this problem.